Penanggulangan Keluarga Terdampak Covid-19 Di Pulau Panjang Kota Batam : Penanggulangan Keluarga Terdampak Covid-19 Di Pulau Panjang Kota Batam - Siti Husaidah; Desi Ernita Amru; Anisya Selvia; Mona Rahayu; Catur Yulinawati (Yayasan Ahmad Mansyur Nasirah, 2021)
Coronavirus Disease 2019 (COVID-19) is a new type of disease that has never been previously identified in humans. This virus has greatly affected the activities of workers, especially low-income people who have lost their main breadwinner due to the corona virus. Indonesia is in the order of 21 COVID-19 cases after Ukraine with 448,118 cases. In severe cases of COVID-19 it can cause pneumonia, acute respiratory syndrome, kidney failure, and even death. The purpose of this service is to teach the community to apply 3M, increase immunity and help ease the burden on families affected by COVID-19, especially casual workers who are infected with COVID-19, both with the status of Patients Under Supervision, People Under Supervision and people without symptoms. The method used in this community service activity is to carry out countermeasures by distributing assistance in the form of basic necessities, health education in increasing family immunity and teaching 3M to the Long Island community. The target of the Long Island community affected by COVID-19 with a target number of 35 families (35 respondents/representatives, a maximum of one person per family). The results of this activity show that the Bulang community, especially housewives, are able to practice ways to prevent the transmission of Covid-19 3M and how to increase immunity by using basic household ingredients such as ginger, temulawak, serre, and turmeric. In addition, the distribution of basic necessities with 35 families can be distributed. Coronavirus Disease 2019 (COVID-19) merupakan jenis penyakit baru yang belum pernah teridentifikasi sebelumnya pada manusia. Virus ini sangat mempengaruhi aktivitas para pekerja, terutama masyarakat ekonomi bawah yang kehilangan pencari nafkah utama akibat virus corona. Indonesia berada pada urutan 21 kasus COVID-19 setelah Ukraina dengan jumlah 448.118 Kasus, Pada kasus COVID-19 yang berat dapat menyebabkan pneumonia, sindrom pernapasan akut, gagal ginjal, dan bahkan kematian. Tujuan dari pengabdian ini adalah untuk mengajarkan masyarakat menerapkan 3M, meningkatkan imunitas serta membantu meringankan beban keluarga terdampak COVID-19, khususnya pekerja lepas yang terinfeksi COVID-19, baik yang berstatus Pasien Dalam Pengawasan, Orang Dalam Pengawasan maupun orang tanpa gejala. Metode yang digunakan dalam kegiatan pengabdian masyarakat ini adalah dengan melakukan penanggulangan dengan menyalurkan bantuan berupa sembako, penyuluhan kesehatan dalam meningkatkan imunitas keluarga dan mengajarkan 3M kepada masyarakat pulau panjang. Sasaran Masyarakat pulau panjang yang terdampak covid-19 dengan jumlah sasaran 35 kk (35 responden/perwakilan maximal satu orang setiap satu kk). Hasil dari kegiatan ini menunjukkan bahwa masyarakat bulang khususnya ibu rumah tangga mampu mempraktekkan cara pencegahan penularan covid-19 3M dan cara meningkatkan imunitas dengan menggunakan bahan dasar rumah tangga seperti jahe, temulawak, serre, dan kunyit. Selain itu, distribusi sembako dengan 35 KK bisa tersalurkan.